2017
DOI: 10.1111/and.12855
|View full text |Cite
|
Sign up to set email alerts
|

Study of the prevalence of 5 HT-2C receptor gene polymorphisms in Egyptian patients with lifelong premature ejaculation

Abstract: We investigated the prevalence of 5HT2C receptor gene polymorphisms in Egyptian patients with lifelong premature ejaculation. A total of 350 participants were enrolled in a prospective study. Two hundred and forty-five cases with lifelong premature ejaculation joined this study, in addition to 105 controls. We instructed the partners of the cases to measure the IELT of the first intercourse only using a stopwatch for 1 month. Genotyping was carried out at the end of the study. The results showed that the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Schmitt et al () showed that 5‐HT reuptake could also take the place of dopamine (DA) and noradrenaline (NE) transporters, which could affect extracellular 5‐HT levels. Several studies revealed that alterations in 5‐HT receptors were also important in sexual performance (Alvarez, Perez, & Artigas, ; Chan et al, ; Foreman, Hall, & Love, ; Roaiah et al, ; Schijven, Sousa, Roelofs, Olivier, & Olivier, ). Hence, the ejaculation reflex may be under the control of interactions between genes and environmental factors (Jannini, Burri, Jern, & Novelli, ; Jannini, Ciocca, et al, ; Jannini, Mario, & Andrea, ).…”
Section: Discussionmentioning
confidence: 99%
“…Schmitt et al () showed that 5‐HT reuptake could also take the place of dopamine (DA) and noradrenaline (NE) transporters, which could affect extracellular 5‐HT levels. Several studies revealed that alterations in 5‐HT receptors were also important in sexual performance (Alvarez, Perez, & Artigas, ; Chan et al, ; Foreman, Hall, & Love, ; Roaiah et al, ; Schijven, Sousa, Roelofs, Olivier, & Olivier, ). Hence, the ejaculation reflex may be under the control of interactions between genes and environmental factors (Jannini, Burri, Jern, & Novelli, ; Jannini, Ciocca, et al, ; Jannini, Mario, & Andrea, ).…”
Section: Discussionmentioning
confidence: 99%
“…PE is also considered as a learned pattern of rapid ejaculation maintained by anxiety about sexual failure (Mccabe, 2005). Previous studies demonstrated that PE was associated with the dysfunction of 5‐hydroxytryptamine (5‐HT) pathway in the brain, which included the hypersensitivity of 5‐HT 1A receptor, as well as the hyposensitivity of 5‐HT 2C receptor (Roaiah et al, 2018; Roaiah et al, 2019). 5‐HT system in the central system is associated with the regulation of emotional processing (Stiedl et al, 2015; Wolf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Different 5‐HT receptors have different biological functions: 5‐HT2C receptor can inhibit ejaculation, while 5‐HT1A receptor can promote ejaculation. Therefore, 5‐HT, 5‐HTT, and 5‐HT receptors are closely related to the occurrence of PE 48 …”
Section: Discussionmentioning
confidence: 99%